Some aspects of the biology of 'ikan kelabau' Osteochilus melanopleura (Bleeker) - Zainal Abidin, Aizam; Saad, Che Roos; Ang, K. J. (Universiti Pertanian Malaysia, 1983)
This study reports on the biology of 'ikan kelabau', Osteochilus melanopleura, a popular indigenous food fish. The length-weight relationship of this fish can be expressed by the equation, Log W = 3.0596 Log L -4.5330. The condition factor was higher during the dry season than during the wet. None of the stomachs examined were empty, suggesting that the fish feeds actively throughout the year. The guts of the juvenile fishes showed substantial quantities of green algae and phytoplankton. Both the maturing and adult 'ikan kelabau' are predominantly herbivores. There is no significant variation in the kinds of good consumed by the various size groups. It was observed that females reached sexual maturity at 290 mm (total length) and the males at 260 mm. This was verified by the histological examination of the gonads. The developmental stages of the oocytes indicated that spawning took place during the wet months between November and March with a peak in February. The gonadosomatic index reached a maximum of 3.1 during this month.